Capacity-building projects in African higher education: Issues of coloniality in international academic collaboration. Issue 2 (1st June 2019) - Adriansen, Hanne Kirstine; Madsen, Lene Møller
Abstract : This article studies issues of coloniality in so-called capacity-building projects between universities in Africa and Scandinavia. Even fifty years after independence, the African higher education landscape is a product of the colonial powers and subsequent uneven power relations, as argued by a number of researchers. The uneven geography and power of knowledge exist also between countries that were not in a direct colonial relationship, which the word coloniality implies. Based on interviews with stakeholders and on our own experiences of capacity-building projects, this article examines how such projects affect teaching, learning, curriculum, research methodology and issues of quality enhancement. We analyse the dilemmas and paradoxes involved in this type of international collaboration and conclude by offering ways to decolonise capacity-building projects.